1-(2,3,4-Trihydroxybenzylidene)thiosemicarbazide - Shawish, H.B.; Maah, Mohd Jamil; Ng, S.W. (International Union of Crystallography, 2010)
In the title molecule, C(8)H(9)N(3)O(3)S, the thiosemicarbazide=N-NH-C(=S)-NH- fragment is twist a different degree of twist in the three independent molecules [dihedral angles = 7.6 (1), 11.6 (1) and 20.7 (1)degrees]. Intramolecular O-H center dot center dot center dot N and O-H center dot center dot center dot O hydrogen bonds occur. In the crystal, the hydroxy and amino groups are hydrogen-bond donors and the O-H center dot center dot center dot O, O-H center dot center dot center dot S and N-H center dot center dot center dot O hydrogen bonds generate a layer motif.